Konseling Apoteker Sebagai Upaya Meningkatkan Kepuasan Pasien Tukak Lambung Di Apotek Kimia Farma - Syifa Alifia Indriani; Hendra Farma Johar (Jurnal Farmasi & Sains Indonesia, 2025)
Pharmaceutical services refer to how "patient care" is delivered. Pharmacist counseling is a crucial component aimed at improving therapeutic understanding and patient satisfaction, particularly in patients with peptic ulcers, who require discipline and adherence to appropriate medication. This study aimed to assess patient satisfaction with services before and after pharmacist counseling regarding peptic ulcers at Kimia Farma pharmacies. The sampling technique used was purposive sampling for peptic ulcer patients, resulting in a sample size of 100 respondents. This study employed a one-group pre-test-post-test and quasi-experimental method. Data analysis used SPSS 29 for Windows and Microsoft Office Excel 2016 to test SERVQUAL values, normality tests, and the Wilcoxon test. The Wilcoxon test demonstrated a significant difference in patient perceptions of the services received before and after pharmacist counseling. The Wilcoxon test also demonstrated a significant difference between expected and actual pharmacy services before and after pharmacist counseling. This indicates that pharmacist counseling has a significant impact on improving patient perceptions and satisfaction with the services received.